Study on multi-scenarios regulating strategy of land use conflict in urban agglomerations under the perspective of “three-zone space”: a case study of Harbin-Changchun urban agglomerations, China - Zheng, Wei; Guo, Bin; Su, Hao; Liu, Zijun (Frontiers in Environmental Science, 2024)
Introduction: Against the background of rapid global urbanization, the urban space expansion has led to increasingly acute land-use conflicts. Accurately understanding the spatial and temporal evolution characteristics of land-use conflict patterns and measuring the level of spatial conflicts are crucial for intensifying sustainable use and management of land resources. Existing research focuses on analyzing the current status of land-use conflicts, while there is limited discussion on tracking spatial-temporal dynamic patterns and simulating future conflict trends. Method: In this paper, the level of spatial conflict was measured by constructing a spatial comprehensive conflict index (SCCI) model, and the spatio-temporal evolution characteristics of land use conflict in Harbin-Changchun urban agglomeration from 2000 to 2020 are discussed. In addition, the PLUS model is used to simulate and predict the pattern of land use conflict in 2030, finally put forward the control strategy. Results: Result shows that: (1) Over the past 20 years, urban space has expanded rapidly with two provincial capitals as growth poles. Land-use conflicts generally exhibit a distribution pattern of “high in the west and low in the east, high in the core and low in the periphery.” (2) During the past 20 years, conflicts have intensified initially and then eased. Severe uncontrolled conflicts are concentrated in the transition zone between urban and rural areas of urban agglomerations. (3) Agricultural space is the core resource and key area contested by different interest subjects in the process of land development and utilization. Discussion: The agricultural space priority scenario proves to be the most effective in controlling spatial conflicts. However, a single space priority scenario cannot adequately address multiple spatial rights and interests. Therefore, different spatial management modes should be implemented in different areas. The purpose of this paper is to provide scientific strategies and suggestions for controlling land-use conflicts in urban agglomerations and achieving sustainable development of regional land use.